Pengembangan Sistem Perantara Pengiriman Data Menggunakan Modul Komunikasi LoRa dan Protokol MQTT Pada Wireless Sensor Network - Haidar Arijuddin; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of Internet of Things is always supported by the WSN (Wireless Sensor Network) concept but the battery power consumption of WSN raises a constant need to lower the energy requirement. LoRa (Long Range) technology acquires low power consumption and broad communication range of more than 2 km, however cannot send data directly to the server. So that a data delivery system is needed to connect between devices at the sensor node to a server called the gateway. The communication between gateway and data centers employs MQTT protocol since it supports the characteristics of IoT such as small bandwidth usage. This research attempted to develop a gateway system in order to connect the sensor nodes and data centers utilizing LoRa communication modules and MQTT protocol. The result of successful rate gateway kinerjance using distance, data size, and different intervals as variables indicates that in range of 400 meters the gateway kinerjance in receiving and forwarding data to data centers is better than the range of 200 meters.